Resting metabolic rate and thermogenic effect of glucose in trained and untrained girls age 11-15 years - Burkhard-Jagodzinska, K.; Nazar, K.; Ladyga, M.; Starczewska-Czapowska, J.; Borkowski, L. (International Journal of Sport Nutrition and Exercise Metabolism, 1999)
Twelve girls who trained in rowing were examined twice a year for 4 years. Their initial age was 11.7 ± (SD) 0.2 yrs. Control groups consisted of 13 girls age 11.5 ± 0.3 yrs and 18 girls age 14.4 ± 0.3 yrs examined simultaneously with trained girls in the first and last year of the study, respectively. The examination involved basic anthropometry, estimation of sexual maturation (Tanner scale), 2-day food records, measurements of resting metabolic rate, energy expenditure following glucose ingestion (50 g), and determinations of blood glucose and plasma insulin concentrations prior to and 2 hrs after glucose load. Body mass, height, and fat content were slightly greater in trained girls. None of the subjects reported disturbances in menstrual function, and the age of menarche was similar for all. Both trained and untrained girls reported similar daily energy intake closer to the lower limit or slightly below the estimates of energy requirements for adolescents. Resting metabolic rate calculated per kg of total body mass or lean body mass was lower in trained girls, while the thermogenic effect of glucose was greater. Plasma insulin concentrations measured 2 hrs after glucose ingestion were lower in trained girls. The results suggest that in circumpubertal girls, increased physical activity leads to energy conservation at rest in postabsorptive state and a tendency toward enhancement of food-induced thermogenesis.